1973
DOI: 10.1001/archpedi.1973.02110190387005
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Poliovirus Immunity Levels in Immunized Illinois Children

Abstract: Antibody titers to poliovirus, measles, and rubella in 504 low-income children in six Il-linois communities were compared with the immunization records of those children. Titers to measles and rubella were, as expected, nearly always present in immunized children, but only one third of children who had received three or more doses of live oral poliovirus vaccine (OPV) had measurable titers to all three polio types. Age, sex, race, age at first OPV, interval between OPVs, and time lapse since last OPV were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Substandard/counterfeit vaccines have been reported, such as vaccines for influenza (153), avian influenza (152), hepatitis B (144), meningitis (151), cholera (56), rabies (154), poliovirus (155), and measles (156) ( Table 6). In one study only 30% of countries that produce vaccines in Asia had internationally acceptable quality control standards (202).…”
Section: Vaccinesmentioning
confidence: 99%
“…Substandard/counterfeit vaccines have been reported, such as vaccines for influenza (153), avian influenza (152), hepatitis B (144), meningitis (151), cholera (56), rabies (154), poliovirus (155), and measles (156) ( Table 6). In one study only 30% of countries that produce vaccines in Asia had internationally acceptable quality control standards (202).…”
Section: Vaccinesmentioning
confidence: 99%
“…Enhancing the stability of vaccines has long been recognized as an important goal for improving the impact of vaccines on world health 1–5. In fact, one of the key factors contributing to the successful eradication of smallpox in 1980 was the availability of heat‐stable vaccine 6.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (Melnick, Burkhardt & Taber, 1969;Rasmussen et al 1973: Rousseau et al 1973 have also reported that vaccine-induced humoral immunity declines substantially in the first 5 years following completion of a course of OPV. With time, therefore, adults might be at an increased risk, regardless of vaccination status.…”
Section: Introductionmentioning
confidence: 99%